2006
DOI: 10.1016/j.bbamcr.2006.06.010
|View full text |Cite
|
Sign up to set email alerts
|

The contraction induced increase in gene expression of peroxisome proliferator-activated receptor (PPAR)-γ coactivator 1α (PGC-1α), mitochondrial uncoupling protein 3 (UCP3) and hexokinase II (HKII) in primary rat skeletal muscle cells is dependent on reactive oxygen species

Abstract: We evaluated the role of reactive oxygen species (ROS) for the contraction induced increase in expression of PGC-1alpha, HKII and UCP3 mRNA. Rat skeletal muscle cells were subjected to acute or repeated electrostimulation in the presence and absence of antioxidants. Contraction of muscle cells lead to an increased H2O2 formation, as measured by oxidation of H2HFF. Acute contraction of the muscle cells lead to a transient increase in PGC-1alpha and UCP3 mRNA by 172 and 65%, respectively (p<0.05), whereas this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 29 publications
7
86
0
6
Order By: Relevance
“…In animal studies, elevation in PGC-1α is associated with fiber-type switch from glycolytic, fast-twitch type 2B/2X to oxidative, slow-twitch type 2A and 1 muscle fibers (Handschin, et al, 2007, Lin, et al, 2002. Expression of PGC-1α was also increased in primary rat skeletal muscle cells after electric stimulation for 90 min a day for 5 days (Silveira, et al, 2006), as well as in C2C12 cells stimulated for 90 min a day for 4 days or after CLF for 24 h (Burch, et al, 2010). In this latter study, expression of several genes involved in oxidative phosphorylation, glucose and fatty acid metabolism increased concomitantly, although not followed by a clear fiber type switch since both MyHC-β and MyHC-2X increased (Burch, et al, 2010).…”
Section: Strategies To Improve the Human Myotube Modelmentioning
confidence: 78%
“…In animal studies, elevation in PGC-1α is associated with fiber-type switch from glycolytic, fast-twitch type 2B/2X to oxidative, slow-twitch type 2A and 1 muscle fibers (Handschin, et al, 2007, Lin, et al, 2002. Expression of PGC-1α was also increased in primary rat skeletal muscle cells after electric stimulation for 90 min a day for 5 days (Silveira, et al, 2006), as well as in C2C12 cells stimulated for 90 min a day for 4 days or after CLF for 24 h (Burch, et al, 2010). In this latter study, expression of several genes involved in oxidative phosphorylation, glucose and fatty acid metabolism increased concomitantly, although not followed by a clear fiber type switch since both MyHC-β and MyHC-2X increased (Burch, et al, 2010).…”
Section: Strategies To Improve the Human Myotube Modelmentioning
confidence: 78%
“…Combined CCA and RSV Treatment Synergistically Increase ROS Signaling and the Induction of Mitochondrial Content in C2C12 Myotubes-ROS-mediated signaling has been shown to be important for the induction of mitochondrial biogenesis (39,40). As Irrcher et al (40) revealed, ROS signaling can induce PGC-1␣ transcription and a resulting increase in mitochondrial biogenesis.…”
Section: Rsv Induces Ampk and P38 Activity In A Temporal Manner That mentioning
confidence: 99%
“…The involvement of ROS in the expression of PGC-1α was first demonstrated in myotube cultures, where the up-regulation of PGC-1α mRNA following acute and chronic electrical stimulation, or hydrogen peroxide incubation was attenuated in the presence of antioxidants or ROS scavengers, respectively (Irrcher et al, 2009;Silveira et al, 2006). Intriguingly, ROS has shown to induce/activate PGC-1α via multiple signalling pathways involving AMPK, p38 MAPK and nitric oxide signalling.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%
“…The disparities in findings within the literature are difficult to reconcile but are potentially related individual differences in response to antioxidant loading and exercise stimulus. Nevertheless, cell culture studies provide direct mechanistic evidence for ROS mediated induction and activation of PGC-1α and as such cannot be discounted as a possible mechanism of mitochondrial biogenesis (Irrcher et al, 2009;Silveira et al, 2006).…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%